THE INFLUENCE OF MODERATING FACTORS IN STUNTING: LOGISTIC PATH ANALYSIS OF ORDINAL DATA - Yulianto, Shalsa Amalia; Solimun, Solimun; Efendi, Achmad; Fernandes, Adji Achmad Rinaldo (PATTIMURA UNIVERSITY, 2025)
Logistic path analysis is used to analyze direct and indirect causal relationships between exogenous-endogenous variables with categorical data types. This study aims to apply logistic path analysis to ordinal categorical data and model the relationship between exogenous variables that affect nutritional status and physical status (stunting) in toddlers in Sumberputih Village, Wajak District. The data used is secondary data obtained from the results of filling out questionnaires in Sumberputih Village at the time of data collection in 2022-2023. The sample used in the study was 100 housewives who had toddlers. The sampling technique used was judgment sampling. However, the study only selected the variables of Birth Weight, Dietary Habits, Nutritional Status, and Physical Status (Stunting). The result of this study is that the variable of Birth Weight has a significant direct effect on Nutritional Status. The variable of Birth Weight has an indirect effect, and the total effect on Physical Status (Stunting) mediated by Nutritional Status is not significant. Meanwhile, the Diet variable has a significant direct effect on Physical Status. In addition, the Socioeconomic Condition variable can moderate the relationship between the Birth Weight variable and Physical Status. The diversity of data that can be explained by the model is 80.36%, while the rest is explained by other variables outside the model by 19.64%.